Isolated infundibular pulmonary stenosis. A case report - K El ouahabi; N Erraboun; A Bouzerda; M Raissouni; I Asfalou; A Benyass; Z Lakhal; Y Moutakillah; M Ait Houssa; E Zbir (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Introduction: Infundibular pulmonary stenosis is one of the numerous pathologic features of the right tract (from the right ventricular outflow tract to the peripheral pulmonary arteries) occurring at the infundibular level. It is usually associated with ventricular septal defect or part of tetralogy of Fallot, but rarely isolated. Methods and results: We report here a case of an adult with isolated infundibular stenosis, and discuss the relative frequency, clinical manifestations, the diagnosis methods, and the results of surgical correction of this lesion. Conclusion: Infundibular pulmonic stenosis with intact ventricular septum is a rare presentation of pulmonary stenosis. Its early detection with a comprehensive examination of the right heart before right ventricular failure is rewarding since it usually can be treated well with a good guidance of surgical management, and low surgical risk.